2017
DOI: 10.1111/scs.12408
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Alzheimer's caregivers in Spain: social, educational and laboral characteristics

Abstract: Being a caregiver implies limitations to entering the job market and for job promotion. There is a generational gap in the caregiver profile, and more and new support services will be needed. Policymakers should take those into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
2
6
0
2
Order By: Relevance
“…On the other hand, a high percentage of the sample is not responsible for care tasks (instrumental exchange). The results of our study related to the profile of the main caregiver are similar to those previously reported in other studies; the main caregiver is characterized as female, a firstdegree relative, married, with primary schooling and in the middle class (Del Pino-Casado et al 2014;Fern andez-Mayoralas et al 2015;Ruiz-Adame et al 2017;Villar-Taibo et al 2016).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, a high percentage of the sample is not responsible for care tasks (instrumental exchange). The results of our study related to the profile of the main caregiver are similar to those previously reported in other studies; the main caregiver is characterized as female, a firstdegree relative, married, with primary schooling and in the middle class (Del Pino-Casado et al 2014;Fern andez-Mayoralas et al 2015;Ruiz-Adame et al 2017;Villar-Taibo et al 2016).…”
Section: Discussionsupporting
confidence: 89%
“…At least part of the difference in Nordic countries is made up by a greater emphasis on formal caregiving. In one Spanish study, 77% of caregivers were women, 61% cared for a parent, and men became caregivers only for their spouse, in old age . In one Polish study, 63% of caregivers were women, and 43% were caring for a parent .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In one Spanish study, 77% of caregivers were women, 61% cared for a parent, and men became caregivers only for their spouse, in old age. (28) In one Polish study, 63% of caregivers were women, and 43% were caring for a parent. (20) In Sweden, 21% of caregivers lived with the care recipient, (25) compared to 80% in Poland.…”
Section: Demographicsmentioning
confidence: 99%
“…The relationship between the listed influencing factors of quantitative evidence (Table 3) and their effect on care-givers’ employment was unambiguous and conclusive in many instances. For example, younger care-givers of PwD were more gainfully employed and worked more hours than older care-givers (Moore et al , 2001; Bakker et al , 2013; Gibson et al , 2014; Ducharme et al , 2016; Schäufele et al , 2016; Hojman et al , 2017; Ruiz-Adame Reina et al , 2017). Other aspects require further analysis.…”
Section: Resultsmentioning
confidence: 99%